Family, lifestyles and new and old type of smoking in young adults: insights from an italian multiple-center study - La Fauci, V.; Mondello, S.; Squeri, R.; Alessi, V.; Genovese, C.; Laudani, N.; Cattaruzza, M. S. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. Tobacco smoke is the epidemic of modern times due to its tremendous burden of diseases and deaths, greater than that produced by alcohol, AIDS, drugs, road accidents, murders and suicides combined. In Italy, 26% of the population smokes and the high prevalence of smoking even among young people is crucial for the Tobacco Industry, because young people are the reservoir which replaces smokers who quit or die. The aim of this study is to investigate smoking habits and determinants of smoking among young adults. Methods. This cross-sectional study enrolled young people from three Italian regions: Latium (central Italy) Calabria (southern Italy) and Sicily (the largest Italian island). An anonymous, multiple-choice online questionnaire was distributed through social networks. Questions investigated individual habits and lifestyles (smoking, alcohol and coffee consumption, physical activity), the presence of smokers in the family and the use of electronic cigarettes. Descriptive and multivariate analyses were used to describe the characteristics of the sample and to evaluate factors associated with smoking status. All statistical analyses were conducted in SAS software version 9.4 (SAS Institute Inc., Cary, NC, USA). All hypothesis tests were 2-tailed and p values <0.05 were considered statistically significant. Results. In a sample of 382 subjects between 18 and 34 years, the prevalence of smoking was 25%. A statistically significant higher percentage of smokers is observed among those who drink coffee and those who drink alcohol. Only 48% of smokers usually smoke classic cigarettes, while 45% roll their own cigarettes and 7% use electronic cigarettes. More than half of the smokers, smoke 1 to 5 cigarettes a day, while 17% smoke over 10 cigarettes a day. In families where there was at least 1 smoker, the percentage of smokers was 34% versus only 15% in families where nobody else smokes. The presence of at least 1 smoker in the family was strongly associated with young adults’ smoking behavior: subjects with family members who smoke were more than three times as likely to be current smokers, compared to those with no family smokers (Odds Ratio [OR] = 3.14, 95% confidence interval [CI] 1.8-5.5, p=0.0001). Alcohol, coffee consumption, unemployment and being a student were also found to be independently and significantly associated with smoking of young adults (alcohol OR=2.96, 95%CI 1.64-5.34; coffee OR= 4.33, 95%CI 1.81-10.39; unemployment OR = 4.76, 95%CI 1.26-17.96; being a student OR = 3.21, 95%CI 1.25-8.27). Conclusions. Preventing young people from smoking is crucial in order to stop the Tobacco Epidemic. The Tobacco Industry is selling new products and is using new marketing tactics (i.e. the “influencers” in social media) which are hooking young people to addictive products and behaviors, thus threatening to wipe out decades of progress in curbing tobacco use. Effective action to drastically reduce new and old types of smoking or to pursue the “Tobacco Endgame” requires an increasing commitment not only towards young people, but also towards families, that play an important role in influencing young people.